The Effect of Fishermen’s Income Factors on Fishermen’s Poverty on The North Coast of Jakarta - Virida Martogi Hasiholan; Akhmad Fauzi; Rilus Ardi Kinseng (Jurnal EMT KITA, 2023)
Poverty still occurs among fishermen amid the abundance of wealth in Indonesia's marine resources, where the substantial coastal and marine potential has not improved the welfare of fishermen's lives. This study aims to determine the poverty level and analyze the factors that affect fishermen's income on the North Coast of Jakarta that cause poverty. This research was conducted in January – February 2023 through a survey with the selection of respondents using stratified-accidental sampling techniques. Respondents in this study amounted to 100 respondents who were taken proportionally at each level. This study's data processing and analysis techniques used poverty-level and multiple linear regression analyses. Based on the research results, the poverty level of fishermen on the North Coast of Jakarta, when compared to the Central Bureau of Statistics poverty line, 44 fishermen out of 100 have incomes below IDR 17.852,00/capita/day. In comparison, when compared to the World Bank poverty line, there are 71 fishermen out of 100 fishermen living below the World Bank poverty line because the income obtained is less than IDR 32.812,00/capita/day. The factors affecting fishermen's income on the North Coast of Jakarta that cause poverty are the size of the boat. In contrast, factors such as age, education level, and work experience do not affect fishermen's income, so these factors do not significantly affect the poverty of fishermen on the North Coast of Jakarta. Knowing that the variable size of the boat significantly affects fishermen's income on the North Coast of Jakarta, it is expected that the Government can provide facilities and infrastructure assistance in the form of boats with larger boat sizes and simplify the application mechanism in obtaining such assistance. So it is hoped that the help of this boat can increase catches for fishermen and increase the income and welfare of fishermen so that the poverty of fishermen on the North Coast of Jakarta can be reduced.